DAMPAK IMPLEMENTASI RGEC TERHADAP NILAI PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Wardoyo ,; Rizki Muti Agustini (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
This research aims to find and analyze influence risk profile, good corporate governance, earnings, and capital on the banking sector companies in Indonesia public company. Based on the completeness of data, there are only 14 banks to the period observation in 2009-2011 that able to be analyzed. The analysis used is multiple regression. The research results show that risk market and risks reputation impact on value of enterprise, while credit risk, risk liquidity, operational risk, risk law, and risks compliance have not been affecting the value of enterprise. Size of the board of commissioners, independence of the board of commissioners, size of the board of directors, and the number of audit committee have not been affecting the value of enterprise. While, ROE impacts on value of enterprise. In the other hands, ROA, BOPO, and CAR values have not been affecting the value of enterprise.Keywords: corporate value, tobin’s Q, risk profile, good corporate governance, earnings.